Analisis perkembangan bank umum syariah pasca pandemi Covid-19 - Marpaung, Reza Rahmad (Maliki Interdisciplinary Journal, 2024)
Sharia banking in Indonesia is experiencing rapid development, driven by the majority of the population embracing Islam and a preference for a usury-free banking system. The Covid-19 pandemic, which began in 2020, had a significant impact on the economy and the performance of the banking sector, including sharia banking. Despite facing major challenges such as decreasing Third Party Funds (DPK) and increasing financing risks, Islamic banking is showing resilience through stable growth in equity financing. The government responded with economic stimulus policies and strengthening risk management. After the Covid-19 pandemic, Islamic banks focused on digitizing health services and protocols which began to bear fruit with recovery and increase in assets in 2021 and 2022. This industry demonstrated the ability to adapt and innovate in the face of the crisis with performance improving slowly but consistently.